2018
DOI: 10.2147/idr.s173456
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of and risk factors for infection with extended-spectrum β-lactamase-producing carbapenem-resistant Enterobacteriaceae: results of a double case–control study

Abstract: PurposeCarbapenem-resistant Enterobacteriaceae (CRE) have been increasingly reported worldwide and pose a serious public threat, but the clinical significance of extended-spectrum β-lactamase (ESBL) production in CRE is not well established.Patients and methodsA retrospective case–case–control study was conducted to identify the clinical characteristics of patients with ESBL-CRE. The susceptibility of isolates obtained from these patients was assessed. The detection of ESBL and carbapenemase-related genes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
1
24
1
1
Order By: Relevance
“…mCIM was used to detect carbapenemase in Enterobacteriaceae and Pseudomonas aeruginosa , whereas eCIM was combined with mCIM to distinguish the Enterobacteriaceae bacteria of metallase- (Ambler B) and serine carbapenemase-producing (Ambler A). The phenotypic results of this study showed that metallase production and serine carbapenemase production are the main drug resistance mechanisms of CRE, which differs from the serine carbapenemase production reported by Tian and Zheng (Zheng et al, 2017; Tian et al, 2018).…”
Section: Discussioncontrasting
confidence: 92%
“…mCIM was used to detect carbapenemase in Enterobacteriaceae and Pseudomonas aeruginosa , whereas eCIM was combined with mCIM to distinguish the Enterobacteriaceae bacteria of metallase- (Ambler B) and serine carbapenemase-producing (Ambler A). The phenotypic results of this study showed that metallase production and serine carbapenemase production are the main drug resistance mechanisms of CRE, which differs from the serine carbapenemase production reported by Tian and Zheng (Zheng et al, 2017; Tian et al, 2018).…”
Section: Discussioncontrasting
confidence: 92%
“…However, in pediatric patients, several studies have reported the predominance or outbreak of bla NDM-1 among CRKP in Beijing, Shanghai and Shandong [2426]. Our previous studies also demonstrated a high prevalence of bla NDM-1 among CRKP in Chongqing [27, 28]. Therefore, more researches are ongoing to uncover the underlying molecular mechanisms of the high prevalence of CRKP in children BSIs and cautious adoption of carbapenems to fight against pediatric CRKP BSI is advocated.…”
Section: Discussionmentioning
confidence: 76%
“…We found that ESBL-EC was often more resistant to quinolones, aminoglycosides (except amikacin) and trimethoprim/sulfamethoxazole, which is consistent with other studies. [9][10][11] The reason may be that plasmids carrying genes encoding ESBL also often carry other drug-resistant genes encoding quinolones, aminoglycosides and trimethoprim/ sulfamethoxazole. 12 Our study found that BTI was an independent risk factor for ESBL-EC BSI.…”
Section: Discussionmentioning
confidence: 99%